Beneficial Effects of Dietary Polyphenols in the Prevention and Treatment of NAFLD: Cell-Signaling Pathways Underlying Health Effects - Echeverría, Francisca; Bustamante, Andrés; Sambra, Verónica; æ#129;lvarez, Daniela; Videla, Luis; Valenzuela, Rodrigo (Current Medicinal Chemistry, 2022)
Background: Non-alcoholic fatty liver disease (NAFLD) is characterized by hepatic accretion of triacylglycerides in the absence of alcohol intake that may progress to steatohepatitis, fibrosis and cirrhosis, becoming the main cause of chronic liver disease. This article discusses recent data concerning the use of dietary polyphenols in the prevention and treatment of NAFLD in vitro, in vivo, and in clinical trials. Methods: Study searches were performed using the PubMed database from the National Library of Medicine-National Institutes of Health. Results: Polyphenols exert beneficial effects in NAFLD, with positive outcomes being related to body weight gain, insulin resistance, liver fat accumulation, oxidative stress, proinflammatory status, mitochondrial dysfunction and ER stress. Data reported for hydroxytyrosol suggest that the activation of the hepatic PPAR-α-FGF21-AMPK-PGC-1α signaling cascade is associated with fatty acid oxidation enhancement, de novo lipogenesis diminution and recovery of mitochondrial function, a contention that is supported by the actions of several polyphenols on specific components of this signaling pathway. Besides, polyphenols downregulate NF-ΚB, suppressing the pro-inflammatory state developed in NAFLD and upregulate liver Nrf2, increasing the cellular antioxidant potential. The latter feature of polyphenols is contributed by chelation of pro-oxidant trace elements, reduction of free radicals to stable forms and inhibition of free radical generating systems. Conclusion: Polyphenols are relevant bioactive compounds in terms of prevention and treatment of NAFLD, which exhibit low bioavailability and instability in biological systems that could limit their health effects. These drawbacks reinforce the necessity of further studies to improve the efficacy of polyphenol formulations for human interventions.
Keywords: polyphenols